Comparing early liver graft function from heart beating and living‐donors: A pilot study aiming to identify new biomarkers of liver injury. (6th April 2017) - Yang, Qi Joy; Kluger, Michael; Goryński, Krzysztof; Pawliszyn, Janusz; Bojko, Barbara; Yu, Ai‐Ming; Noh, Keumhan; Selzner, Markus; Jerath, Angela; McCluskey, Stuart; Pang, K. Sandy; Wąsowicz, Marcin
Abstract: The liver and kidney functions of recipients of liver transplantation (LT) surgery with heart beating (HBD, n  = 13) or living donors (LD, n  = 9) with different cold ischemia times were examined during the neohepatic phase for the elimination of rocuronium bromide (ROC, cleared by liver and kidney) and tranexamic acid (TXA, cleared by kidney). Solid phase micro‐extraction and LC–MS/MS was applied to determine the plasma concentrations of ROC and TXA, and creatinine was determined by standard laboratory methods. Metabolomics and the relative expressions of miR‐122, miR‐148a and γ‐glutamyltranspeptidase (GGT), liver injury biomarkers, were also measured. The ROC clearance for HBD was significantly lower than that for LD (0.147 ± 0.052 vs. 0.265 ± 0.148 ml·min −1 ·g −1 liver) after intravenous injection (0.6 mg·kg −1 ). The clearance of TXA, a compound cleared by glomerular filtration, given as a 1 g bolus followed by infusion (10 mg·kg −1 ·h −1 ), was similar between HBD and LD groups (~ 1 ml·min −1 ·kg −1 ). The TXA clearance in both groups was lower than the GFR, showing a small extent of hepatorenal coupling. The miR‐122 and miR‐148a expressions were similar for the HBD and LD groups, whereas GGT expression was significantly increased for HBD. The lower ROC clearance and the higher GGT levels in the HBD group of longer cold ischemia times performed worse than the LD group during the neophase. Metabololmics further showed clusters of bile acids, phospholipids and lipid ω‐oxidation products for the LD and HBD groups. In conclusion, ROC CL and GGT expression, and metabolomics could serve as sensitive indices of early graft function. Copyright © 2017 John Wiley & Sons, Ltd.